Anemia in adolescent girls - Gulrukh Bakhramova Bakhtiyar's Qizi (Genius Journals, 2023)
Chronic menorrhagia in adulthood is a common gynecological disease among adolescents. Persistent menopause is associated with anemia and infertility. Prolonged menstruation in puberty is a common gynecological condition among adolescents. Long-term menorrhagia can cause severe anemia and even infertility. Taking iron supplements during menstruation can help teenage girls regulate their periods and effectively reduce premenstrual pain symptoms.
Keywords: Adolescent girls; body; pain; energy improvement